2023
DOI: 10.1111/nph.18698
|View full text |Cite
|
Sign up to set email alerts
|

Plasma membrane‐associated calcium signaling modulates cadmium transport

Abstract: Summary Cadmium (Cd) is a toxic heavy element for plant growth and development, and plants have evolved many strategies to cope with Cd stress. However, the mechanisms how plants sense Cd stress and regulate the function of transporters remain very rudimentary. Here, we found that Cd stress induces obvious Ca2+ signals in Arabidopsis roots. Furthermore, we identified the calcium‐dependent protein kinases CPK21 and CPK23 that interacted with the Cd transporter NRAMP6 through a variety of protein interaction t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(10 citation statements)
references
References 84 publications
(125 reference statements)
0
8
0
Order By: Relevance
“…Previous research has suggested that Ca may play a role in reducing Cd absorption and translocation in rice through signal transduction from ACA . A recent study revealed that Ca-dependent protein kinases ( CPK 21 and CPK 23 ) act as Ca sensors and can improve Cd tolerance in plants by inhibiting the activity of the Cd transporter Nramp6 . This work suggested that seed priming can regulate Cd absorption by altering the expression levels of various ACAs pathways.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Previous research has suggested that Ca may play a role in reducing Cd absorption and translocation in rice through signal transduction from ACA . A recent study revealed that Ca-dependent protein kinases ( CPK 21 and CPK 23 ) act as Ca sensors and can improve Cd tolerance in plants by inhibiting the activity of the Cd transporter Nramp6 . This work suggested that seed priming can regulate Cd absorption by altering the expression levels of various ACAs pathways.…”
Section: Resultsmentioning
confidence: 90%
“…61 A recent study revealed that Cadependent protein kinases (CPK 21 and CPK 23) act as Ca sensors and can improve Cd tolerance in plants by inhibiting the activity of the Cd transporter Nramp6. 62 This work suggested that seed priming can regulate Cd absorption by altering the expression levels of various ACAs pathways. However, there is limited research on how Cd transporters react with ACAs regulation, and additional investigations are required in the future.…”
Section: Expression Changes Of Genes In Transmembranementioning
confidence: 97%
“…Extensive research has been conducted on the mechanism of Cd tolerance in Arabidopsis plants [ 23 , 24 ]. Researchers have found that endo-beta mannase MAN7 can regulate Cd tolerance by regulating the cell wall binding capacity of Arabidopsis roots [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have found that endo-beta mannase MAN7 can regulate Cd tolerance by regulating the cell wall binding capacity of Arabidopsis roots [ 23 ]. In addition, Cd tolerance can be regulated by regulating calcium signal transduction related to the plasma membrane [ 24 ]. These results provide new insights for the molecular breeding of crops for Cd tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…The Mn transporters possess different subcellular localization and functions, which are crucial for maintaining intracellular Mn homeostasis. In addition, the activities and locations of these Mn transporters are strictly and precise regulated by Ca 2+ signaling at the translation level (Zhang et al 2021b(Zhang et al , 2023aFu et al 2022;Ju et al 2022).…”
Section: Introductionmentioning
confidence: 99%